Medical Termination of Delayed Miscarriage: Four-Year Experience with an Outpatient Protocol - Joana Lyra; João Cavaco-Gomes; Marina Moucho; Nuno Montenegro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose To evaluate the efficacy of an outpatient protocol with vaginal misoprostol to treat delayed miscarriage. Methods Retrospective analysis of prospectively collected data on women medically treated for missed abortion with an outpatient protocol. The inclusion criteria were: ultrasound-based diagnosis of missed abortion with less than 10 weeks; no heavy bleeding, infection, inflammatory bowel disease ormisoprostol allergy; nomore than 2 previous spontaneous abortions; the preference of the patient regarding the medical management. The protocol consisted of: 1) a single dose of 800 μg of misoprostol administered intravaginally at the emergency department, after which the patients were discharged home; 2) clinical and ultrasonographic evaluation 48 hours later - if the intrauterine gestational sac was still present, the application of 800 μg of vaginal misoprostol was repeated, and the patients were discharged home; 3) clinical and ultrasonography evaluation 7 days after the initiation of the protocol - if the intrauterine gestational sac was still present, surgical management was proposed. The protocol was introduced in January 2012. Every woman received oral analgesia and written general recommendations. We also gave them a paper form to be presented and filled out at each evaluation. Results Complete miscarriage with misoprostol occurred in 340 women (90.2%). Surgery was performed in 37 (9.8%) patients, representing the global failure rate of the protocol. Miscarriage was completed after the first misoprostol administration in 208 (55.2%) women, with a success rate after the second administration of 78.1% (132/169). The average age of the women with complete resolution using misoprostol was superior to the average age of those who required surgery (33.99 years versus 31.74 years; p = 0.031). Based on the ultrasonographic findings in the first evaluation, the women diagnosed with fetal loss achieved greater success rates compared with those diagnosed with empty sac (p = 0.049). Conclusions We conclude this is an effective and safe option in the majority of delayed miscarriage cases during the first trimester, reducing surgical procedures and their consequences.